Data sovereignty and the cloud – a structured bibliography - Vaile , David (Journal of Telecommunications and the Digital Economy, 2019)
This set of references includes documents assisting understanding of the late-2013 status of cloud and data sovereignty (or “digital protectionism”) policy discussions in Australia. Material from the US, EU and other countries is necessarily less complete than that from Australia. Some online material may require registration or subscription. Links were active in October 2013.